The Relationship Between Delinquents, Their Primary Environment and Police - Vileikienė, Eglė (Sociologija. Mintis ir veiksmas, 2005)
The article presents sociological research of the at-risk child’s and police officers. By this research the relationships between the at-risk child’s and those police officers directly working with them is analyzed. In addition the following are concerned in causes of delinquency and the relationship between delinquents and their parents, peer group and teachers. The collected data interpretation is based on the contemporary criminological theories.